127 CHARACTERISTICS AND TREATMENT OF 2346 PATIENTS WITH STABLE CORONARY ARTERY DISEASE IN UK PRIMARY CARE. (24th May 2013) - Kalra, P R; Zachariah, D; Greenlaw, N; Ford, I; Fox, K
Abstract : Background: Coronary artery disease(CAD) is a leading cause of death within the UK. Elevated resting heart rate (HR) is a consistent predictor of adverse prognosis in patients with cardiovascular disease. There remains a paucity of data on the characterisation and management of outpatients with CAD. The aim of the study was to describe a representative cohort of patients with stable CAD within UK primary care with a particular focus on HR and β-blocker usage. Methods: CLARIFY (ProspeCtive observational LongitudinAl RegIstry oF patients with stable coronary arter Y disease) is a global study of patients with stable CAD (defined as prior myocardial infarction, MI, or revascularization procedure, evidence of coronary stenosis of >50%, or chest pain associated with proven myocardial ischaemia). A total of 33 438 patients from 45 countries were enrolled between November 2009 and July 2010. Within the UK 2346 patients were recruited from 250 GP practices each providing 10 consecutive patients and they form the current study population. Patients were evaluated according to resting HR (≤60 bpm, 61–69 bpm and ≥70 bpm) and use of β-blockers. Multi-variable analysis of independent predictors of HR≥70 bpm was performed using a logistic regression model. This cut-off was selected based on results of several studies showing it to be an important prognostic threshold. Results: Mean age of the population was 67.4±9.2(SD) years, 75.7% were male, 18% had diabetes and 56% treated hypertension. 66% were on β-blockers, 87% aspirin, 58% ACE inhibitors, 18% angiotensin receptor blockers and 95% lipid lowering drugs. Demographics according to HR are shown in table 1. HR≥70bpm was also associated with worse angina class when present, higher diastolic blood pressure(BP), diabetes and not having had coronary angiography. In a multivariate model, HR≥70 bpm was independently predicted by female gender, diabetes, smoking, sedentary life style, increased alcohol intake, atrial fibrillation/atrial flutter, asthma/COPD, increased diastolic BP and those without PCI. Demographics according to β-blocker use are shown in table 2. β-Blockers were used more in those with current angina, treated hypertension and lower left ventricular ejection fraction; use was also associated with lower diastolic blood pressure BP, lower cholesterol and higher use of aspirin, lipid lowering drugs and ACE inhibitors. 40% of patients not on a β-blocker had symptoms indicative of intolerance or contra-indication to them. Conclusions: Although 65.6% of patients with stable CAD in the UK are prescribed β-blockers, 37.2% still have a resting HR≥70 bpm, a level shown to be associated with adverse prognosis. This is despite almost half of the patients with HR≥70 bpm already being on a β-blocker. Whilst it appears that further HR lowering is possible in many patients with stable CAD it remains uncertain as to whether it will improve outcomes.